The Effect of Good Corporate Governance and Environmental Performance on Financial Performance of the Proper Listed Company on Indonesia Stock Exchange - Andriana, Abigail; Panggabean, Rosinta Ria (Binus Business Review, 2017)
This research aimed to determine whether the environmental performance and Good Corporate Governance (GCG) mechanisms, such as managerial ownership, institutional ownership, the proportion of independent commissioners had effects of the audit committee on measured financial performance by using Return on Equity (ROE). This research population was manufacturing company listed on Indonesia Stock Exchange that participated in PROPER 2012/2013 and 2013/2014. Based on the multiple regression analysis, audit committee partially had a significant effect on financial performance, while the others did not. Meanwhile, the analysis result shows that environmental performance and all GCG mechanisms simultaneously have significant effects on financial performance.